Peritoneal Dialysis in Acute Kidney Injury: Prescribing Acute PD - Ponce, Daniela; Balbi, André Luís [UNESP] (Springer Nature, 2021)
Decades ago, peritoneal dialysis was widely accepted as treatment for acute kidney injury (AKI); however, its usage declined in favor of other types of extracorporeal therapies. The interest in PD to manage AKI patients has been reignited, and PD now frequently is used in developing countries because of its lower cost and minimal requirements for infrastructure. Studies from Brazil, India, and Africa have shown that with careful thought and planning, critically ill patients can be successfully treated with PD. To overcome some of the classic limitations in the use of PD for AKI, such as increased risk of infectious and mechanical complications and poorer control of urea, potassium, and bicarbonate levels, the use of cyclers, flexible catheters, and a high volume of dialysis fluid has been proposed. However, in developing countries, the setup for quality research is often lacking, thereby resulting in limited evidence regarding standardized treatment regimens including indications, dosing, technical failure, and mortality. The recent publication of the International Society for Peritoneal Dialysis (ISPD) guidelines for PD in AKI has tried to address these issues and provide an evidence-based standard by which to provide therapy. In this chapter, the advances in technical aspects, advantages, and limitations of PD and the key prescriptions and strategies for PD use in AKI are discussed, and we will review recent literature on clinical experience with PD for the treatment of AKI.
Keywords: Acute kidney injury; Indications; Limitations; Peritoneal dialysis; Prescription